Neuroanatomy in clinical context : an atlas of structures, sections, systems, and syndromes - Haines, Duane E. (Philadelphia : Wolters Kluwer Health, 2015)
Succeed in your neuroanatomy course with Neuroanatomy: An Atlas of Structures, Sections, and Systems, Ninth Edition. This premiere learning resource provides everything you need to master course content, including clear explanations; a thorough synopsis of functional components, tracts, pathways, and systems; superb, high-quality MRI, CT, MRA, and MRV images; abundant color illustrations and photographs; hundreds of review questions; a wide range of clinical correlates; and a host of interactive online resources. To prepare you for exams and rotations, the atlas emphasizes the application of neuroanatomy concepts in clinical settings. Prepare for the boards with a wide range of multiple-choice USMLE-style review questions (with extensive explanations) and a vast online interactive question bank. Fine tune your understanding with innovative color illustrations that show clinical images of representative lesions integrated with the corresponding deficits. Prepare for rotations with color illustrations of pathways, lesions, and brain slices integrated with clinical images. Visualize structures as they appear both to the unaided eye and on imaging studies with superb MRI images. Build your clinical understanding with MRI/CT images that provide the clearest and most clinically relevant views of key structures using the latest imaging modalities. Test your understanding with the assessment section in Chapter 10 that serves as a practice test for neuroanatomy. Take your learning beyond the book with online resources, including interactive Q & A andinteractive atlas/labeling. Provided by publisher.
Introduciton and user's guide -- External morphology of the central nervous system -- Cranial nerves -- Meninges, cisterns, ventricles, and related hemorrhages -- Internal morphology of the brain in unstained slices and MRI -- Internal morphology of the spinal cord and brain: functional components, MRI, stained sections -- Internal morphology of the brain in stained sections: axial-sagittal correlations with MRI -- Tracts, pathways, and systems in anatomical and clinical orientation -- Herniation syndromes: brain and spinal dics -- Anatomical-clinical correlations: cerebral angiogram, MRA, and MRV -- Q&As: a sampling of study and review questions, many in the USMLE style, all with explained answers.
Preceded by Neuroanatomy / Duane E. Haines. 8th ed. c2012.
Includes bibliographical references and index.
Keywords: Central Nervous System -- anatomy & histology -- Atlases; Neuroanatomy -- Atlases; Neuroanatomy